An assessment of the impact of ISO 9000 certification on company performance in Philippine manufacturing companies - Marquez, Charlie A.
This study presents an elevation of the effectiveness of ISO 9000 standards as applied in the Philippine setting it is based on the assessment of quality managers and quality management representatives who were directly involved in the process of obtaining ISO 9000 certification. A comparison on the performance of companies before and after certification was performed and companies certified to ISO 9000 were profiled to be able to assess the impact of ISO 9000 certification in Philippine manufacturing companies.